Integration Of Spiritual Values In The Leadership Of Madrasah Principals - Anis Zohriah; Anis Fauzi; Eman Sulaiman; Abdullah Muqopie; Mikdar Rusdi (The Faculty of Education and Teaching Training, 2025)
Madrasahs really need mastery of spiritual values in the performance process to strengthen the practice of worship in a narrow sense and in a broad sense, so that all attitudes, speech, actions and even certain social skills contain elements of worship. Principal leadership requires mastery of spiritual values as work guidelines and also the development of life values in the context of managing educational institutions. This study aims to examine the opportunities and challenges of applying the concept of spiritual leadership for madrasah principals and school principals. This study uses a literature study approach or literature review, by examining various literature sources in the form of books, journals, research reports and procedings from international seminars. The results showed that the spiritual leadership of madrasah principals is a prerequisite that must be fulfilled by prospective madrasah principals and becomes a value and moral that must be upheld by the entire madrasah community. The spiritual leadership of the principal becomes a guideline in behavior, action, speech and social skills development, for the entire school community towards meaningful education.